Experiences and lessons from structural interventions against COVID-19 in Addis Ababa, Ethiopia - Engdawork, Kibur; Amdework, Ezana; Assefa, Samuel; Ayode, Desta; Tadele, Getnet (Frontiers in Sociology, 2024)
Introduction: Fighting pandemics like COVID-19 requires implementing successful structural interventions that attempt to change the social and political environments to increase adherence to preventive behaviour among community members. However, studying structural interventions during pandemics and their challenges remains to be uncharted territory in developing countries. Objectives: Given this, we documented the experiences of implementing such interventions in Ethiopia with the aim of drawing lessons for future efforts to fight similar outbreaks in resource limited and low-income settings. Methods: We conducted a qualitative study between September and October 2021. Data were collected through face to face and telephone interviews from purposefully selected stakeholders from government and private sectors engaged in social interventions to prevent COVID-19. The systematization and the analysis of the data were conducted with MAXQDA 2020 software. Results: Ethiopia tried to respond to the COVID-19 pandemic through structural and social interventions. This included: developing national policy and guidelines, mainstreaming COVID-19 interventions to local organizations, implementing capacity development programs, and developing strategies to engage the community, through traditional institutions, in intervention activities. In addition, a mass communication approach was used to deliver risk messages. This yielded a promising result in slowing down the spread of COVID-19 in the most populated city of the country. On the other hand, competing interests, misconceptions, capacity constraints among 2 professionals and organizations, limited legislation enforcing capacity and lack of motivation for change from the community side affected the implementation and the outcomes of interventions. Conclusion: Stakeholder shall take these challenges into consideration when designing and implementing structural interventions to contain disease outbreaks effectively. The study implied that attempts to withstand pandemic in low-and middle-income settings shall successfully utilize local resources, act swiftly when pandemics outbreak and adjust themselves to the dynamic challenges and limitations of structural interventions.